THE IMPACT OF SOCIAL MEDIA ON STUDENTS' EFFECTIVE TIME MANAGEMENT - Nana Katsitadze; Natalia Kharadze; Dea Pirtskhalaishvili (Baltic Journal of Economic Studies)
The ability to manage time effectively has been demonstrated to have a significant impact on individuals' daily performance and achievements. However, it is important to note that the improper use of social media has the potential to hinder effective time management. The present study focuses on the students of Ivane Javakhishvili Tbilisi State University, Faculty of Economics and Business, and School of Tourism and Hospitality. The survey garnered a total of 908 respondents. The study was undertaken in recognition of the significance of the issue and the challenges that respondents face in this area. The objective was to establish the influence of social media use on respondents' time management. The research results indicate that the surveyed respondents allocate a significant amount of time to social media usage. Due to the study's limitations, further research will be conducted to analyse results from various leading universities in Georgia. The research was conducted using quantitative methods, employing an anonymous questionnaire comprising 44 closed questions. The respondents were permitted to express their opinions at the conclusion of the questionnaire. Quantitative research facilitated the survey of a substantial number of students, thereby enabling the establishment of reasonable recommendations. During the research process the following hypotheses have been developed: Hypothesis 1. Using a time management model (Q18_1) will affect the ability to balance study and leisure (Q21_1); Hypothesis 2. Self-control over smartphones during work/study time (Q 29_1) will significantly affect the ability to balance study and leisure (Q21_1); Hypothesis 3. Spending more than four hours per day online using social media (Q 31) negatively affects work-life balance (Q21_1) and academic performance (Q24_1); Hypothesis 4. Spending more than four hours per day online using social media (Q 31) leads to deviance from plan Q26_1.